Correlation between optical coherence tomography and multifocal electroretinogram findings with visual acuity in retinitis pigmentosa - Moschos MM (Dove Medical Press, 2013)
Marilita M Moschos, Irini P Chatziralli, George Verriopoulos, Aristeides Triglianos, Dimitrios S Ladas, Dimitrios BrouzasLaboratory of Electrophysiology, First Department of Ophthalmology, University of Athens, Athens, GreeceIntroduction: Our purpose was to study the correlation between the macular morphology and function in eyes with retinitis pigmentosa (RP).Methods: Sixty-six eyes from 33 patients with RP and with different visual acuity (VA) were studied using optical coherence tomography (OCT) and multifocal electroretinogram (mfERG). Correlation analysis was performed between VA, macular thickness, mfERG amplitude, and latency.Results: Retinal thickness, retinal response density, and latency of the mfERG in the foveal area were independently and positively associated with VA (P = 0.002; P < 0.0001; P = 0.029; and P = 0.002, respectively), whereas there was no evidence for a correlation between VA and the amplitude of mfERG in the parafoveal area. Evidence of a correlation between the OCT and the mfERG evaluation was of borderline significance (P = 0.047). Also, there was evidence for an inverse association of VA with latency in ring 1 and ring 2 (b = -0.138; 95% confidence interval: -0.261, -0.015; P = 0.029). In accordance with the univariate findings, when foveal retinal thickness, mfERG amplitude, and latency in ring 1 were inserted simultaneously in the same model, all the three variables remained significantly associated with VA (P = 0.016; P < 0.0001; and P = 0.031, respectively). Nevertheless, some individual values deviated from the expected range. More specifically, 15 eyes showed a normal retinal thickness, whereas the respective VA was relatively low and the mfERG values were abnormal. Conversely, in seven eyes, despite the low retinal thickness, the respective VA was high.Conclusion: The combined use of OCT with mfERG appears to be more appropriate for the estimation of macular function.Keywords: retinitis pigmentosa, OCT, mfERG, VA